ANALISIS NILAI-NILAI KEARIFAN LOKAL CERITA MASYARAKAT KABUPATEN MELAWI TERHADAP PENGUATAN PENDIDIKAN KARAKTER BANGSA MAHASISWA PGSD STKIP MELAWI - Joni Albar; Deki Wibowo; Astrid Nabila (Bestari: Jurnal Pendidikan dan Kebudayaan, 2024)
This research aims to analyze the local wisdom values embedded in the folk stories of Melawi Regency's community and how these values can contribute to strengthening the national character education for students of the Primary School Teacher Education Program (PGSD) at the Teachers College of Melawi (STKIP Melawi). The research methodology employed is a qualitative approach with data collection techniques through interviews, observations, and document analysis. The research sample encompasses traditional community stories that are still preserved by the people of Melawi Regency. The gathered data is analyzed using content analysis techniques to identify the local wisdom values present in the stories. The findings reveal that the folk stories of Melawi Regency's community contain various local wisdom values, such as moral values, ethics, solidarity, honesty, and respect for nature and fellow human beings. These values hold significant potential for reinforcing the national character education for PGSD students at STKIP Melawi. The integration of local wisdom values into the PGSD curriculum can be achieved through the development of learning modules, extracurricular activities, and field experiences that allow students to delve into and practice these values in their daily lives. Thus, PGSD students will be able to become agents of change who are capable of embodying and teaching local wisdom values to the younger generation through formal education in primary schools